2021
DOI: 10.3390/diagnostics11122220
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Genomic Analysis of Proteasome 20S Subunit Alpha (PSMA) Family Members in Breast Cancer

Abstract: The complexity of breast cancer includes many interacting biological processes, and proteasome alpha (PSMA) subunits are reported to be involved in many cancerous diseases, although the transcriptomic expression of this gene family in breast cancer still needs to be more thoroughly investigated. Consequently, we used a holistic bioinformatics approach to study the PSMA genes involved in breast cancer by integrating several well-established high-throughput databases and tools, such as cBioPortal, Oncomine, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 84 publications
(85 reference statements)
1
20
0
Order By: Relevance
“…Meanwhile, this matches the result of the disruption of the T-cell methionine metabolic pathway by tumor cells ( Bian et al, 2020 ). Furthermore, PSMA8 predicts favorable outcomes in cancer and is associated with immune response signaling, which corresponded with our study ( Chiao et al, 2021 ). In addition, PSMB2 shares the same conclusion with PSMA8.…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, this matches the result of the disruption of the T-cell methionine metabolic pathway by tumor cells ( Bian et al, 2020 ). Furthermore, PSMA8 predicts favorable outcomes in cancer and is associated with immune response signaling, which corresponded with our study ( Chiao et al, 2021 ). In addition, PSMB2 shares the same conclusion with PSMA8.…”
Section: Discussionsupporting
confidence: 92%
“…Some of the strongest gains in 15q included TMED3, IMP3, PSMA4 and RCN1 . In the context of breast cancer, TMED3 and RCN1 overexpression promote proliferation 48,49 , IMP3 is associated with EMT 50 and PSMA4 correlated with poorer survival 51 . The basal phenotype in breast cancer is an aggressive type associated with poor prognosis, that typically expresses genes associated with proliferation 52 and EMT 53 .…”
Section: Resultsmentioning
confidence: 99%
“…Proteasome dysfunction leads to many cardiovascular diseases, including cardiomyopathies, heart failure, and atherosclerosis. 46 , 47 In aneurysms, proteasome peptidase activity was increased in both human and mouse abdominal AA tissue, which could be inhibited by bortezomib, a potent, selective inhibitor of the chymotrypsin-like activity of the 20S proteasome. Additionally, studies have demonstrated that low-dose bortezomib injection appeared to reduce MMP activity, smooth muscle cell phenotypic switching, and elastin degradation, resulting in the attenuation of aneurysm formation.…”
Section: Discussionmentioning
confidence: 99%